PHYTOCHEMICAL STUDY OF Tiquilia PARONYCHOIDES (PHIL) A. RICHARDSON "FLOWER OF SAND" - Tomás Ch., Gloria (2002)
The present research refers to Tiquila paronychoides(flor de arena). By phitochemistrey analysis has been determined the following compounds: tanins, flavonoids, alcaloids and ester [acid grass) which was isolated. The ester was characterizated by lnfrared Spectroscopy and Nuclear Magnetic Resonance Spectroscopy 1H-NMR and 13C-NMR